Cyclic codes over F2 + uF2 + vF2 + v2F2 with respect to the homogeneous weight and their applications to DNA codes - Bulut Yilgor, Merve; Gursoy, Fatmanur; Oztas, Elif Segah; Demirkale, Fatih (SPRINGER, 2021)
In this paper, we study cyclic codes and their duals over the local Frobenius non-chain ring R = F-2[u, v]/ , and we obtain optimal binary linear codes with respect to the homogeneous weight over R via a Gray map. Moreover, we characterize DNA codes as images of cyclic codes over R.
Keywords: Cyclic codes; Codes over rings; Homogeneous weight; DNA codes; MOLECULAR COMPUTATION; CHAIN RINGS; FINITE; ENCRYPTION; SEQUENCE; WEIGHT; Computer Science; Mathematics